PERLINDUNGAN HUKUM KONSUMEN TERHADAP PENARIKAN DAN PENYITAAN OBJEK JAMINAN FIDUCIA YANG TIDAK DIDAFTARKAN KREDITUR - Ramdhani, Fahmi Ali (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2021)
The facts on the ground are that there are often problems due to legal consequences due to the non-registration of fiduciary guarantees by financial institutions. This study aims to determine consumer legal protection measures when fiduciary collateral is not registered at the Fiduciary Registration Office. This study also aims to examine the legal consequences of the withdrawal and confiscation of fiduciary collateral objects that are not registered at the Fiducia Registration Office by PT. Suzuki Finance Indonesia. This study uses a normative juridical method with descriptive-analytical research specifications through a statutory approach. Based on this study, it is concluded that consumer dispute resolution can be pursued through the court or outside the court based on the decision of the disputing parties. One of the legal protections and obligations in using fiduciary guarantees for finance companies was the first issuance of PP No.21 of 2015, Permenkeu No. 130 / PMK.010 / 2012, and POJK 29/2014. The legal consequence of not registering the object of the fiduciary guarantee is that the fiduciary guarantee has not been born so that the legal consequences attached to the fiduciary guarantee do not apply.